Use of cetrorelix in the investigation of testosterone excess in a postmenopausal woman. (26th April 2011) - Chantler, Donna J; Gordon, Derek; Millan, David; Panarelli, Maurizio
Abstract : A 65-year-old woman presented to the endocrine clinic with increasing facial hirsutism over the past 6 months. She was noted to have excess hair on forearms, back and abdomen, along with some frontal balding. There were no abnormalities of the external genitalia, blood pressure was satisfactory and weight was stable. Biochemistry confirmed elevated testosterone (4.1 nmol/l). No abnormalities were seen on CT of abdomen and pelvis, nor by transvaginal ultrasound of the ovaries. Six months after her initial clinic visit, testosterone had increased to 6.0 nmol/l, rising to 7.3 nmol/l a few months later. Testosterone failed to suppress to low-dose dexamethasone suggesting excessive adrenal production was unlikely. Urine steroid profiling revealed no abnormality of adrenal steroid metabolites. Testosterone suppression was achieved with a rapidly-acting luteinizing-hormone-releasing hormone antagonist (cetrorelix), suggesting an ovarian source of excess production. Histology following bilateral salpingo-oophorectomy revealed a benign 6 mm diameter Leydig cell tumour in the right ovary.